2020
DOI: 10.2147/dmso.s273339
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison of Diabetes-Dependent Quality of Life (ADDQoL) in Patients with T2DM in Poland, The Czech Republic, and Slovakia</p>

Abstract: The purpose of the paper was to perform a comparative analysis of the impact of T2DM on QoL, including specific ADDQoL domains and associations between QoL, selected socio-demographic factors (including gender, age, education, residence, marital status, professional activity) or clinical parameters (HbA1c levels, fasting blood glucose, BMI, duration of DM, complications, treatment used), in adult diabetic patients from Poland, the Czech Republic and Slovakia. The study group included 608 patients diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In this study, the mean score of diabetes-dependent quality of life indicates a relatively good quality of life in our T2DM patients. The results of Krzeminska et al showed that ADDQoL in T2DM patients in Poland, the Czech Republic, and Slovakia was good or very good (21). Further, "good," "very good," and "excellent" levels of the present general quality of life were declared by 65% of women and 52% of men with T2DM in Bak et al study (22).…”
Section: Discussionmentioning
confidence: 96%
“…In this study, the mean score of diabetes-dependent quality of life indicates a relatively good quality of life in our T2DM patients. The results of Krzeminska et al showed that ADDQoL in T2DM patients in Poland, the Czech Republic, and Slovakia was good or very good (21). Further, "good," "very good," and "excellent" levels of the present general quality of life were declared by 65% of women and 52% of men with T2DM in Bak et al study (22).…”
Section: Discussionmentioning
confidence: 96%
“…When QoL and/or satisfaction with treatment are affected by the therapeutic regimen, it may have a negative impact on the perception of the quality of life and cause an increase in the risk of complications. [2] Such factors as patient's beliefs, attitude towards the disease and acceptance of the limitations imposed by it are important factors in the self-assessment of the quality of life in patients with type 2 diabetes. The assessment of the quality of life and the disease makes it possible to identify the actual problems and observations of patients as well as their needs.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Restrictions related to compliance with therapy rules based on diet, regular use of medications or insulin therapy and optimal physical activity combined with blood glucose measurements can result [4] in a negative impact of diabetes on the quality of life in patients. [5] Gender differences are an important factor in the assessment of the health-dependent quality of life because gender plays a major role in decisions concerning health, as well as in the perception of health in different countries and cultures. [6] Poland, Czech Republic, and Slovakia are neighboring countries with similar economic status and cultural behavior patterns, which is why the authors decided to conduct this type of assessment in these countries.…”
Section: Introductionmentioning
confidence: 99%